2003
DOI: 10.1159/000068367
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Cytometric Cellular Allergen Stimulation Test in Latex Allergy

Abstract: Background: The use of flow-cytometric basophil activation to different allergens has been recommended in recent years. In this study, we analyzed the diagnostic reliability of the flow-cytometric allergen stimulation test (FAST) after latex-specific stimulation in vitro. The diagnostic reliability of the technique was assessed as well as its correlation with other in vitro diagnostic parameters. Methods: 43 patients allergic to latex with a positive history and skin test participated in the study. Thirty subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 23 publications
4
38
0
2
Order By: Relevance
“…As an alternative to SPT, with its inherent safety risks, the BAT was used in this study to measure the relative ability of the WT Ags, rHev b 6.01 mutants, and Hev b 6.02 peptide variants to activate basophils. Although BAT is recognized as a very sensitive and specific assay for the diagnosis of latex allergy (43), there have been no direct comparisons of BAT and skin prick testing with recombinant latex proteins. Although it has been reported that 1 to 10 ng/ml recombinant latex allergen will elicit a positive SPT response (38), we found a lack of activation of basophils with 10 g/ml rHev b 6.01 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to SPT, with its inherent safety risks, the BAT was used in this study to measure the relative ability of the WT Ags, rHev b 6.01 mutants, and Hev b 6.02 peptide variants to activate basophils. Although BAT is recognized as a very sensitive and specific assay for the diagnosis of latex allergy (43), there have been no direct comparisons of BAT and skin prick testing with recombinant latex proteins. Although it has been reported that 1 to 10 ng/ml recombinant latex allergen will elicit a positive SPT response (38), we found a lack of activation of basophils with 10 g/ml rHev b 6.01 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, diagnosis of NRL anaphylaxis can readily be established by quantification of sIgE (k82), skin tests, or both (77)(78)(79). Although these tests are highly reliable, results of are not always unequivocal (80), and some patients might need additional tests such as basophil activation (81)(82)(83) or challenge tests (84,85) to establish diagnosis.…”
Section: Natural Rubber Latexmentioning
confidence: 99%
“…Moreover, as we have previously described [7]neither the results of the Basotest nor the IgE level were correlated with the patient’s sensitivity assessed by skin prick test (results not shown) and clinical history. Several studies [13, 14, 15]have evaluated the interest of flow cytometry basophil stimulation tests in the same setting (table 2). Similar specificity values were reported [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies utilized different thresholds of positivity: Sanz et al [13]calculated the threshold value at 10% using ROC curves, Boumiza et al [14]determined the positivity by 2 sequential latex dilutions inducing an increase of more than 10% above control levels and Ebo et al [15]estimated the threshold at 17% using ROC curves as well.…”
Section: Discussionmentioning
confidence: 99%